Comparison of maximum voluntary isometric contraction of the quadriceps muscle after modified hybrid training with NMES in untrained healthy subjects - Budiawan, Putri Ayu Madedi; Tinduh, Damayanti; Prawitri, Yudith Dian; Melaniani, Soenarnatalina (Edelweiss Applied Science and Technology, 2025)
Reduced muscle strength is often caused by decreased of physical activity and sedentary lifestyle. Neuro-Muscular Electrical Stimulation (NMES) Russian Protocol and hybrid training system are alternative methods for strengthening exercises to increase muscle strength. This study aimed to analyze the effect of Hybrid modification strengthening exercise and Russian NMES protocol on Quadriceps Femoris muscle strength in healthy untrained subjects. Twenty-four subject, untrained healthy male aged 25-45 years, divided into the Modified Hybrid Training (MHT) Group (n=12) and the Neuro-Muscular Electrical Stimulation (NMES) Group (n=12). Both groups received intervention 3 times per week for 4 weeks (12 sessions). Maximum Voluntary Isometric Contraction (MVIC) of quadriceps muscle measured before and after intervention. There was improvement in the MVIC of quadriceps muscle in MHT group (dominant limb p = 0.001, non-dominant limb p = 0.001) and NMES group (dominant limb p = 0.001, non-dominant limb p < 0.001). There was no significant difference in the change of MVIC (ΔMVIC) of the quadriceps muscle between the Hybrid method and NMES groups on both legs. Both Modified Hybrid Training (MHT) and the Neuro-Muscular Electrical Stimulation (NMES) are effective in increasing quadriceps muscle MVIC with comparable result.